2019
DOI: 10.28998/rca.v17i1.6522
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field and Gibberelic Acid as Pre-Germination Treatments of Passion Fruit Seeds

Abstract: <p>The aim of this study was to evaluate the effect of pre-germination treatments (magneto-priming and immersion of seeds in gibberellic acid solution) on variables associated with germination, emergence and vigor of Passiflora edulis seeds ‘BRS Gigante Amarelo’ cultivar. Seeds were extracted from fruits, washed, immersed for 6 hours in solutions with different GA3 concentrations and later arranged in a circular form in Petri dishes at temperature of 25°C, with and without exposure to magnetic field. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The significant difference between the treated seeds using the magnetic field and those without treatment was presented by Osorio, Aranzazu-Osorio Carbonell-Padrino (2015), who used magneto priming in tomato and soybean seeds. The same result was achieved by Menegatti et al (2019) in passion fruit seeds.…”
Section: Table 2: Statistical Results Of Germination (%)supporting
confidence: 80%
See 2 more Smart Citations
“…The significant difference between the treated seeds using the magnetic field and those without treatment was presented by Osorio, Aranzazu-Osorio Carbonell-Padrino (2015), who used magneto priming in tomato and soybean seeds. The same result was achieved by Menegatti et al (2019) in passion fruit seeds.…”
Section: Table 2: Statistical Results Of Germination (%)supporting
confidence: 80%
“…The magneto-priming technique increased germination speed compared to the control treatment (no exposure of seeds to MF), suggesting a certain influence of MFs on the processes of water absorption by seeds, a fact that may have resulted in increased speed and uniformity of the germination process (Osorio;Aranzazu-Osorio;Carbonell-Padrino, 2015). The alteration of the water properties (with greater circulation capacity) and the possible action on the cell membrane permeability allow elucidation of the mechanism of magnetic field action on seed germination promotion (Menegatti et al, 2019).…”
Section: Table 2: Statistical Results Of Germination (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…and reported a linear increase in the average germination rate, coefficient of germination rate, and water absorption with increasing the MF intensity. Moreover, Menegatti et al [ 8 ] indicated that the exposure of passion fruit seeds to the MF in an isolated way stimulated seed germination, emergence, and vigor. Magnetically treated chickpea ( Cicer arietinum L.) seeds showed an improvement in seed performance in terms of germination speed and length, and dry weight seedling, and the response varied with field strength and duration of exposure [ 36 ].…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
“…The effects of the MF in seeds and plants have made impressive advances in the last 10 years in plant science. Currently, there is real evidence that magnetic pre-germination treatment of seeds before sowing allows for reduced costs of planting as germination rates are increased substantially, as well as the plant growth being promoted [6][7][8]. However, others showed that development is inhibited [9,10].…”
Section: Introductionmentioning
confidence: 99%